All-cause mortality after hypoglycemic and hyperglycemic emergencies among U.S. adults with diabetes, 2011–2020. (March 2023) - McCoy, Rozalina G.; Herrin, Jeph; Galindo, Rodolfo J.; Sindhu Swarna, Kavya; Umpierrez, Guillermo E.; Hill Golden, Sherita; O'Connor, Patrick J.
Abstract: Estimated all-cause mortality within 30-days of hypoglycemic emergencies is 0.8 % in adults with type 1 diabetes and 1.7 % with type 2 diabetes; and within 30-days of hyperglycemic emergencies, it is 1.2 % with type 1 diabetes and 2.8 % with type 2 diabetes. These rates changed little between 2011 and 2020.